Information Systems and Their Influence on Effective Decision-Making in Government Administration: A Systematic Literature Review - Mohammad Sohaib Saqib; Baz Mohammad Nazari; Rohullah Aimaq (Gameology and Multimedia Expert, 2026)
This study examines the role of Management Information Systems (MIS) in organizational decision-making, with particular focus on Afghan organizations. Effective decision-making increasingly depends on accurate, timely, and relevant information, yet many organizations in developing countries still rely on manual methods that cause delays, errors, and weak decision outcomes. This paper adopts a systematic literature review (SLR) methodology, synthesizing 30 academic sources on MIS, decision quality, and organizational performance in developing-country contexts, interpreted against the Afghan public and private sector. The analysis shows that MIS improves decision quality by increasing the speed of report generation, reducing manual data-entry errors, and strengthening inter-departmental coordination. Established theoretical models consistently explain how system and information quality translate into better managerial decisions. However, implementation in developing countries such as Afghanistan is constrained by unreliable infrastructure, limited technical skills, resistance to change, weak management support, and poor data quality. The paper concludes that investment in infrastructure, continuous localized training, leadership commitment, and simplified user interfaces can substantially improve MIS performance and organizational decision quality, offering practical guidance for policymakers, organizational leaders, and IT managers in resource-constrained environments